Maximizing recovery time between knock-out races improves sprint cross-country skiing performance - McGawley, K.; Van Waerbeke, C.; Westberg, K. J.; Andersson, E. P. (Journal of Sport and Health Science, 2022)
Background In a sprint cross-country (XC) ski competition, the difference in recovery times separating the first and the second semi-final (SF) heats from the final (F) may affect performance. The aim of the current study was to compare the effects of longer vs. shorter recovery periods prescribed between the 3 knock-out races of a simulated sprint XC ski competition involving a prologue (P), quarter-final (QF), SF, and F.